2019
DOI: 10.1016/j.gca.2019.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of solid-state clumped isotope reordering in carbonate minerals from aragonite heating experiments

Abstract: The clumped isotope compositions of carbonate minerals are subject to alteration at elevated temperatures. Understanding the mechanism of solid-state reordering in carbonate minerals is important in our interpretations of past climates and the thermal history of rocks. The kinetics of solid-state isotope reordering has been previously studied through controlled heating experiments of calcite, dolomite and apatite. Here we further explore this issue through controlled heating experiments on aragonite. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…It is possible that this transition results in disequilibrium Δ 47 compositions that are colder than predicted. Such behaviour has been observed during controlled laboratory heating experiments when aragonite transforms to calcite 51 . In this case, we can rule out a clumped isotope effect during the ikaite-calcite transition because the Δ 47 values of the primary (type I) calcite are indistinguishable from the concretionary calcite (type II), which did not experience such a transition.…”
Section: Discussionmentioning
confidence: 65%
“…It is possible that this transition results in disequilibrium Δ 47 compositions that are colder than predicted. Such behaviour has been observed during controlled laboratory heating experiments when aragonite transforms to calcite 51 . In this case, we can rule out a clumped isotope effect during the ikaite-calcite transition because the Δ 47 values of the primary (type I) calcite are indistinguishable from the concretionary calcite (type II), which did not experience such a transition.…”
Section: Discussionmentioning
confidence: 65%
“…Because clumped-isotope resetting in biogenic aragonites occurs at much lower temperatures than those required for solid-state reordering on the same timescales (Henkes et al, 2014;Passey & Henkes, 2012) and the aragonite-calcite phase transition (Chen et al, 2019;Staudigel & Swart, 2016), we hypothesize that this process operates prior to and alongside solid-state reordering. During a simple burial heating scenario (i.e., temperatures increasing over time), these fluid-carbonate exchange reactions would be expected to occur prior to solid-state reordering.…”
Section: Discussionmentioning
confidence: 98%
“…Clumped‐isotope analyses of biogenic aragonite materials that were heated (Müller, Staudigel, et al., 2017; Staudigel & Swart, 2016) have revealed that biogenic aragonite is more susceptible to internal resetting of clumped isotopes (∆ 47 ) than calcite (Passey & Henkes, 2012) or abiogenic aragonite (Chen et al., 2019). This susceptibility to alteration at lower temperatures has provided a potentially useful tool for reconstructing the thermal histories of aragonitic bivalves found in archeological contexts, giving insight into ancient cooking methods (Müller, Staudigel, et al., 2017; Staudigel et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Carbonate mineral precipitation under closed system conditions is unlikely, because the high δ 13 C values of the precipitates indicate CO 2 degassing and the low δ 18 O values indicate a meteoric water origin. We exclude effects of mineral transition 41 due to lack of recent hydrothermal activity at Erzberg and experimental evidence against low temperature influence of carbonate mineral transition on clumped isotope signatures 42,43 .…”
Section: Discussionmentioning
confidence: 99%